若∫f(x)=3e2x+C ,则f ( x ) = ( )A.2 e6x B.1/2e6x C.6 e2x D.1/6e
1个回答
f(x)=3e^(2x)*(2x)'=3e^(2x)*2=6e^(2x)
选C
相关问题
若∫f(x)e^1/xdx=e^1/x+C,则f(x)= A,-1/x B,-1/x^2 C,1/x D,1/x^2 请
若f(x)=xe的x次方,则y'(1)=?A.e B.2e C.3e D.4e
f(x)=e^2x +4e^x -6x+a (0
已知函数f1(x)=e^|x-2a+1|,f2(x)=e^(|x-a|+1),x∈R,1≤a≤6
设f(x)=lnx,若f'(x0)=2,则x0=?A、e² B、e C、ln2/2 D、ln2
.1.∫f(x)dx=(e^x)cos2x+c,则f(x)= A.(e^x)(cos2x-2sin
设X的为随机变量,则 E(2X-3)= a.2E(X) B.4E(X)-3 C.2E(X)+3 D.2E(X)-3
设f(x)=[e^x+e^(-x)]/2,g(x)=[e^x-e^(-x)]/2,计算f(1)g(3)+g(1)f(3)
若f(x)=e−1x,则limt→0f(1−2t)−f(1)t=−2e−2e.
f(x)=e^x-e^-x,g(x)=e^x+e^-x,e=2.71,(1){f(x)}^2+{g(x)}^2的值?